Visual continuous time preferences - Prissé, Benjamin (Frontiers in Behavioral Economics, 2023)
We introduce the Visual Continuous Time Preferences (VCTP) task, a new tool for measuring time preferences that synthesizes the simplicity of Multiple Price List (MPL) and the precision of Convex Time Budget (CTB) tasks. We evaluate VCTP in a lab experiment by comparing it to MPL using the same experimental design. Results suggests that VCTP effectively measures time preferences and enhances their precision without increasing task time or decreasing subject consistency. We also find that the BRIS payment scheme has an impact on outcomes, compared to hypothetical and real payments.